Case Report: Anti-LGI1 Limbic Encephalitis Associated With Anti-thyroid Autoantibodies - Otiniano-Sifuentes, Ricardo; Cuba Antezana, Anali; De La Cruz Ramirez, Walter F.; Pacheco-Barrios, Kevin; Segura Chavez, Darwin A. (Frontiers in Neurology, 2021)
Anti-LGI1 encephalitis is an autoimmune encephalitis with antibodies against leucine-rich glioma-inactivated 1 (LGI1), first described in 2010. It is a non-frequent and poorly understood entity that represents the second most frequent cause of autoimmune encephalitis. This entity is characterized by the presence of limbic encephalitis, hyponatremia, and faciobrachial dystonic seizures. Herein, we present the case of a male patient with an onset of epileptic seizures (generalized tonic-clonic seizure), and involuntary dystonic movements that affect the right side of his face and right upper limb associated with mental disorder, and affectation of higher functions. The electroencephalogram showed continuous generalized cortical-subcortical dysfunction. The brain magnetic resonance imaging showed signal hyperintensity at the level of both mesial temporal lobes and hippocampi and in the head of the right caudate nucleus. Anti-thyroglobulin antibodies were positive, and he was initially diagnosed as Hashimoto's encephalopathy (HE). However, the response to corticosteroids was not completed as it is usually observed in HE. For that, antibodies for autoimmune encephalitis were tested, and the anti-LGI1 antibodies were positive in serum and cerebrospinal fluid. HE is an important differential diagnosis to consider. Furthermore, the presence of Anti-thyroglobulin antibodies should not be taken as the definitive diagnostic criteria, since these antibodies could be associated with other autoimmune encephalopathies, which include in addition to anti-LGI1, anti-NMDA and anti-Caspr2.